Kemapuan Berfikir Kritis Anak Usia 5-6 Tahun TK Pertiwi Kecamatan Bone Kabupaten Bone Bolango - Nurhasanah H. Basumbang; Rapi Us Djuko; Sri Rawanti (Inovasi Pendidikan dan Anak Usia Dini, 2024)
The purpose of this research is to find the impact of Project Based Learning on the Critical Thinking Skills of 5-6 Years Old Children. This is a quatitative experimental research (One Group Pretest-post-test). The Population of this research consists of 12 children, and the sample is 12 group B children aged 5-6 years at Tk Pertiwi, Bone Subdistrict, Bone Bolango Regency. The Data analysis technique uses stastistics data processing. The results showed an increase in the average pre-test, obtaining a score of 59.84, and the resuld of the average value of the negative difference is (-21.28091). Meanwhile, the average post-test is 81.62. Therefore, it shows a significant difference between the pretest and posttest scores with a p-value of 0.000, so the hypothesis results are” confirmed,” where the significant value of 0.000, <alpha value of 0.05. In other words, H0 is rejected and H1 is confirmed. It can be conluded that projct-based learning impacts the criticalthinking ability of 5-6 year old children at Pertiwi Kindergarten, Bone District, Bone Bolango Regency.